Investigation of microfluidics filtration and separation - Tan, Jian Hao. (2013)
Microfluidics filtration and separation has been an integral part of microfluidics in the recent years, offering a wide range of applications like DNA analysis, bio-defense, medical diagnostic applications etc. Further investigation of the performance of these microfilter devices will aid the course of future studies and development.